THE IMPACT OF CASH TURNOVER, RECEIVABLE TURNOVER, INVENTORY TURNOVER, CURRENT RATIO AND DEBT TO EQUITY RATIO ON PROFITABILITY - AMANDA, REZANA INTAN (INDONESIAN RESEARCH SOCIETY, 2019)
The purpose of this research is to analyze the impact of Cash Turnover, ReceivableTurnover, Inventory Turnover, Current Ratio and Debt to Equity Ratio to Profitability. Thesample in this study is the Basic Chemical Industry Sector at the Indonesia Stock Exchangein 2013-2017. Population of the research is the Basic Chemical Industry Sector on IDXfinancial report which is taken with certain criteria. The number of samples in this study wasdetermined based on Purposive Sampling method, and determined the number of samplesas much as 8 company. Based on the results and data analysis using step regression(helped by software SPSS.16 for windows) shows that Cash Turnover has no impact toProfitability, Receivable Turnover has no impact to Profitability, Inventory Turnover has noimpact to Profitability, Current Ratio has a positive and signification impact to Profitability,Debt to Equity Ratio has no impact to Profitability.